Optimization of Vertical Axis Darrieus Wind Turbine As Aerator Generator - Musyafiq, Afrizal Abdi; Illahi , Novita Asma; Purwiyanto; Vicky Prasetia; Hera Susanti (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Research has focused on a wind turbine system with a vertical-axis Darrieus design with a capacity of 15 watts, serving as an aerator for aeration or adding air to water. The Darrieus turbine, made of aluminium with three corners and a modified NACA 0018 model optimized to work at low wind speeds of 2 m/s, effectively powers a 4-watt DC aerator. Generator voltage readings show a minimum value of 2 volts at a wind speed of 1 m/s and a maximum value of 12.8 volts at a wind speed of 6.2 m/s. The calculated power coefficient is 0.3. Charging the accumulator with a 12 volts/12 Ah takes 23 hours with a generator voltage of 13 volts at a wind speed of 6 m/s. This research reflects Indonesia's progress in optimizing wind energy for sustainable power generation.